Issues of Islamic preaching in Tafsir al-Qur’an al-karim - Ahmad, Nadzrah; Solihin, Sohirin Mohammad; Amir, Ahmad Nabil (Faculty of Islamic Studies, Universiti Kebangsaan Malaysia (UKM), 2017)
This paper discusses issues and ideas of Islamic preaching in kitab Tafsir al-Qur’an al-Karim by al-Ustaz H. A. Halim Hasan, H. Zainal Arifin Abbas and Abdur Rahim Haitami. It attempts to highlight the topic of dakwah as projected in the tafsir and expounding its essential themes and views. In defining and investigating the ideas and principles of dakwah it refers to arguments brought forth in classical and modern works of tafsir that set forth in-depth discussions concerning its framework and methods in the Qur’an. The research aims to investigate issues of dakwah as described in Tafsir al-Qur’an al-Karim and probe into its conclusion and jurisprudence (fiqh). It employed descriptive and analytical method to elucidate the exegete views of the groundwork and idealism of dakwah in the Qur’an. The study concludes that kitab Tafsir al-Qur’an al-Karim essentially emphasize on the strategic discourse (khitab) of dakwah in the Qur’an emphasizing on its jurisprudence and method and its essential relevance to expand Islamic works and dakwah movements in Sumatera and Indonesian Muslim community at large.